Environmental impact assessment of aluminium production using the life cycle assessment tool and multi-criteria analysis - Javad Abdollahi; Nima Emrani; Benyamin Chahkandi; Ali Montazeri; Reza Aghlmand; Mohammad Gheibi (Annals of Environmental Science and Toxicology - Peertechz Publications, 2021)
Air pollution is one of the most important problems of urban life. Since a large proportion of airborne pollutants originate from industry, it is important to address emission removal systems. One of the growing industries is the production of aluminum, which requires attention and planning since emits dangerous pollutants such as particulate matter, SO2, NOx, dioxins, furans, mercury chloride, and fluorine compounds. The present study investigates the production life cycle of this metal and analyzes the production of gaseous pollutants and particles in different production units. Large amount of pollution is produced in the alumina production and the aluminum electrolysis units, which in the best case, for the production of one ton of final aluminum, Emit 1.07, 4.73, and 1.32 kg of particulate pollutants, sulfur dioxide, and nitrogen dioxide respectively. In the next step, in the search of the optimal system for controlling particulate pollutants, SO2, NOx caused by aluminum production, by reviewing the research background and related articles and books, ranked these systems using ELECTRE, TOPSIS and SAW methods. Sedimentation chamber, internal separators, cyclones, fabric filters, electrostatic precipitators, and wet collectors in particle removal and condensation, absorption, adsorption, incineration, and wet washing in SO2 and NOx removal were reviewed and compared. The results show the superiority of cyclones in particle removal, wet washing system for removing SO2, and adsorption for removing NOX.